2014
DOI: 10.1007/s00204-014-1240-8
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor CHOP, a central component of the transcriptional regulatory network induced upon CCl4 intoxication in mouse liver, is not a critical mediator of hepatotoxicity

Abstract: Since xenobiotics enter the organism via the liver, hepatocytes must cope with numerous perturbations, including modifications of proteins leading to endoplasmic reticulum stress (ER-stress). This triggers a signaling pathway termed unfolded protein response (UPR) that aims to restore homeostasis or to eliminate disturbed hepatocytes by apoptosis. In the present study, we used the well-established CCl4 hepatotoxicity model in mice to address the questions whether CCl4 induces ER-stress and, if so, whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
4
33
0
2
Order By: Relevance
“…Gene array analysis performed on the livers of rats facilitated the differentiation between genotoxic and non-genotoxic carcinogens (Ellinger-Ziegelbauer et al 2008;. These successful toxicogenomics studies in vivo prompted several ambitious research programs, including the EU-funded SEURAT-1 network and the ESNATs project Krug et al 2013;Schug et al 2013;Weng et al 2014;Balmer et al 2014;Campos et al 2014), with the aim to identify biomarkers of toxicity in vitro. One long-term goal of these projects is to identify biomarkers in the in vitro systems that can predict certain mechanisms of toxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Gene array analysis performed on the livers of rats facilitated the differentiation between genotoxic and non-genotoxic carcinogens (Ellinger-Ziegelbauer et al 2008;. These successful toxicogenomics studies in vivo prompted several ambitious research programs, including the EU-funded SEURAT-1 network and the ESNATs project Krug et al 2013;Schug et al 2013;Weng et al 2014;Balmer et al 2014;Campos et al 2014), with the aim to identify biomarkers of toxicity in vitro. One long-term goal of these projects is to identify biomarkers in the in vitro systems that can predict certain mechanisms of toxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CHOP was not 363 significantly reduced in mouse livers exposed to PFOA in the presence of 4-PBA even 364 though serum concentrations of ALT and AST were significantly reduced. Indeed, a recent 365 study has suggested that genetic depletion of CHOP does not protect mice against 366 CCl 4 -induced liver injury [44]. These findings implied that other potential, unidentified 367 signals were involved in cell death resulting from ER stress.…”
mentioning
confidence: 99%
“…CHOP expression was not paralleled with TMCs apoptotic level, suggesting that CHOP expression may not directly result in cell death. Furthermore, CHOP can regulate GADD34 expression [46], so the moderate expression of CHOP in TMCs from IgAN group may be associated with GADD34 maintenance.…”
Section: Discussionmentioning
confidence: 99%